Development of Web-Based E-Learning on Virus Material in Biology Education Study Program - Ulviah, Arifah; Aziz, Andi Asmawati; Daud, Firdaus (Universitas Pahlawan Tuanku Tambusai, 2025)
This development research (Research and Development) aimed to evaluate the characteristics, validity, practicality, and effectiveness of website-based e-learning for virus material in the Biology Education Study Program at Muhammadiyah Bulukumba University, using the ADDIE model comprising Analyze, Design, Development, Implementation, and Evaluation stages. Designed for easy access on digital devices, the e-learning incorporates multimedia features such as images, text, animations, sound, and videos, enhancing engagement and learning effectiveness. The e-learning demonstrated high validity, though improvements in language and coherence are needed for optimal results. It also received positive feedback on practicality from lecturers and students for its ease of use. Effectiveness was evident in improved student outcomes, with pretest scores rising from an average of 59.95 to 85.67 in the posttest. Overall, the e-learning was deemed valid, practical, and effective, with recommendations for large-scale trials and development of additional materials to further enhance its utility.